Four-dimensional carbon-ion pencil beam treatment planning comparison between robust optimization and range-adapted internal target volume for respiratory-gated liver and lung treatment. (December 2020) - Kanai, Takayuki; Paz, Athena; Furuichi, Wataru; Liu, Ching-Sheng; He, Pengbo; Mori, Shinichiro
Highlights: Two motion management techniques: 4DRO and rITV, were compared. rITV approach was more conservative to preserve target dose. 4DRO plan could improve the OAR dose, while preserving acceptable target coverage. Abstract: We investigated the dose differences between robust optimization-based treatment planning (4DRO) and range-adapted internal target volume (rITV). We used 4DCT dataset of 20 lung cancer and 20 liver cancer patients, respectively, who had been treated with respiratory-gated carbon-ion pencil beam scanning therapy. 4DRO and rITV plans were created with the same clinical target volume (CTV) and organs at risk (OAR) contours. Four-dimensional dose distribution was calculated using deformable image registration. Dose metrics (e.g. D95, V20) were analyzed. Statistical significance was assessed by the Wilcoxon signed-rank test. For the lung cases, the mean CTV-D95 value for the rITV plan (=98.5%) was same as that for the 4DRO plan (=98.5%, P = 0.106), while the mean D95 value for the CTV + setup margin contour for the rITV plan (=98.2%) was higher than that for the 4DRO plan (95.2%, P < 0.001). For the liver cases, the mean CTV-D95 value for the rITV plan (=98.1%) was slightly lower than that for the 4DRO plan (=98.5%, P < 0.01), while the mean D95 value for the CTV + setup margin contour for the rITV plan (=98.0%) was higher than that for the 4DRO plan (94.1%, P < 0.001). For the doses to the organs at risk (OARs), the ipsilateral lung-V20/liver-V20 values for the rITV plan (=10.1%/19.7%) was significantly higher than that for the 4DRO plan (=8.6%/17.6, P < 0.001). Although the target coverage for 4DRO plan may be worse than that for rITV plan in the presence of the setup error, the 4DRO plan can improve OAR dose while preserving acceptable target dose coverage.